Актуальні проблеми навчання та виховання дітей в інклюзивному освітньому середовищі - Кузава, Ірина; Kuzava, Irina (Східноєвропейський національний університет імені Лесі Українки, 2016)
У статті здійснено аналіз актуальних проблем навчання та виховання дітей в інклюзивному освітньому середовищі. Розкрито сутність і зміст понять «інклюзія» та «інтеграція», які в сучасних дослідженнях мають синонімічну змістову наповненість, що не завжди відповідає термінологічній. Визначено та проаналізовано основні відмінності інклюзивної освіти від інтегрованої. Обґрунтовано важливі чинники ефективної реалізації інклюзивної освіти, зокрема, позитивне ставлення до спільної взаємодії вихованців із різним рівнем психофізичного розвитку педагогічних та управлінських кадрів, батьків тощо. The article analyzes the actual problems of education and upbringing of children in inclusive educational environment. The essence and meaning of "inclusion" and "integration", which in the present study are synonymous semantic fullness that do not always meet the terminological. The basic difference of integrated inclusive education. A number of obstacles in the implementation of inclusive education as: a small number of special pre-schools network (s) at the place of residence of persons of this category; shortage of places in the overall preschool education for these students; insufficient provision of relevant qualified personnel in the field of inclusive education; unavailability (psychological, professional) society, comprehensive pre-schools, teachers to accept these children and work with them in terms of inclusion; lack of program-methodical, logistical support inclusive education of preschool children requiring correction of mental and physical development; insufficient consolidation efforts of professionals, parents, scientists in the field of medical and psycho-pedagogical support of preschool children with mental and physical disorders; availability interdepartmental barriers in the organization of joint training and education of preschool children; lack of early diagnosis and comprehensive medical, psychological and educational support. Important factors proved effective implementation of inclusive education, in particular, a positive attitude to joint interaction of students with different levels of mental and physical development of teaching and administrative staff, parents and others.
Actual problems of education and upbringing of children in inclusive educational environment
Keywords: інклюзія; інтеграція; інклюзивне навчання; інтегроване навчання; готовність об’єктів та суб’єктів інклюзивної освіти до спільної взаємодії; inclusion; integration; inclusive education; integrated training facilities and the readiness of inclusive education for joint cooperation